2020
DOI: 10.1007/s41130-020-00124-w
|View full text |Cite
|
Sign up to set email alerts
|

Health, air pollution, and animal agriculture

Abstract: for useful comments or discussions. Nicolas Treich acknowledges financial support from the ANR under grant ANR-17-EURE-0010 (the Investissements d'Avenir program), INRAE and the FDIR chair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The global simulation showed that agriculture, largely due to animal farming, is the largest contributing sector to PM 2.5 in eastern United States, Russia, East Asia, and Europe. 46 , 47 For instance, food-related PM 2.5 pollution caused 15,900 annual deaths in the United States. About 80% of these deaths could be attributable to animal-based food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global simulation showed that agriculture, largely due to animal farming, is the largest contributing sector to PM 2.5 in eastern United States, Russia, East Asia, and Europe. 46 , 47 For instance, food-related PM 2.5 pollution caused 15,900 annual deaths in the United States. About 80% of these deaths could be attributable to animal-based food.…”
Section: Discussionmentioning
confidence: 99%
“…48 A 50% decrease in agricultural ammonia emissions would reduce annual PM 2.5 concentration levels by 11%, 8%, and 5% in Europe, North America, and East Asia respectively. 47 Promoting the plant-based dietary pattern at the population level may be a cost-effective strategy for decreasing the relevant burden of diseases induced by air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…More than 55% of P M 2.5 emissions in France originate from the residential and tertiary sector, while 15% originate from the transport sector (Lavaine et al, 2020;Citepa, 2022). By contrast, N O x emissions primarily originate from the transport sector (58%).…”
Section: Air Pollutionmentioning
confidence: 99%
“…However, we can also imagine cases where π(ω) is increasing with ω. For instance, intensive farming might contribute to air pollution leading to health externality (Lavaine et al, 2020). In this case, consumers might selfishly benefit from restrictions on intensive farming.…”
Section: Human Utilitiesmentioning
confidence: 99%